改进差异演化算法在机械优化设计中的应用 - 李高扬; 吴育华; 刘明广 (Jixie Chuandong, 2006)
Differential evolution algorithm is applied to optimization problem of mechanical design and the basal theory and steps are analysed. At the same time, double best mutation operation and chaos migration operation are proposed to improve differential evolution algorithm’s optimized performance. The algorithm is tested through two mechanical design numerical cases and the simulated result shows differential evolution algorithm has rapid speed of convergence and strong steadiness.